2021
DOI: 10.2174/1381612826666201029100151
|View full text |Cite
|
Sign up to set email alerts
|

DLX6-AS1: An Indispensable Cancer-related Long Non-coding RNA

Abstract: Background: There is increasing evidence that lncRNA, a type of transcript which is over 200 nucleotides in length may serve as oncogenes or suppressor genes are implicated in the pathophysiology of human diseases. In particular, tumorigenesis and progress are closely correlated with its abnormal expression. In addition, it may become a promising target for many oncology biotherapies. Abnormal DLX6-AS1 expression affects different cellular processes such as proliferation, aggression and metastasis. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This lncRNA plays a crucial role in a range of biological processes, such as regulating tumour proliferation, migration and invasion. 179 Tumour‐derived exosomes can be ingested by macrophages in the tumour microenvironment and eventually promote tumour progression and metastasis. 180 There are some reports on the functions of HCC‐derived exosomes in human cancers.…”
Section: Competing Endogenous Rna Network (Cerna)mentioning
confidence: 99%
See 1 more Smart Citation
“…This lncRNA plays a crucial role in a range of biological processes, such as regulating tumour proliferation, migration and invasion. 179 Tumour‐derived exosomes can be ingested by macrophages in the tumour microenvironment and eventually promote tumour progression and metastasis. 180 There are some reports on the functions of HCC‐derived exosomes in human cancers.…”
Section: Competing Endogenous Rna Network (Cerna)mentioning
confidence: 99%
“…DLX6‐AS1 has been demonstrated to function in tumours by ceRNA for binding to and inhibiting the function of miRNAs. This lncRNA plays a crucial role in a range of biological processes, such as regulating tumour proliferation, migration and invasion 179 . Tumour‐derived exosomes can be ingested by macrophages in the tumour microenvironment and eventually promote tumour progression and metastasis 180 .…”
Section: Competing Endogenous Rna Network (Cerna)mentioning
confidence: 99%
“…LncRNAs are composed of at least 200 nucleotides, are easily detectable in human body fluids, and their binding and expression are highly specific. Several recent studies have shown that the differential expression of lncRNAs is related to PCa [ 139 , 140 , 141 ]. Throughout this topic, cell-free lncRNAs with potential application in the diagnosis and prognosis of this malignant disease will be discussed and summarized in Table 2 .…”
Section: Pancreatic Cancer Diagnosis and Prognosis By Cell-free Rnasmentioning
confidence: 99%
“…In osteosarcoma, lncRNAs distal-less homeobox 6 antisense 1 (DLX6-AS1) was highly expressed in osteosarcoma tissue and cell lines [ 123 , 127 , 128 ]. Moreover, its expression was significantly correlated with advanced TNM stage, tumor grade, distant metastasis and poor prognosis [ 123 , 127 ].…”
Section: Regulatory Network Of Lncrnas and Wnt Signaling Pathway In Osteosarcomamentioning
confidence: 99%